Geographic Variation in Health Care Utilization and Outcomes in Veterans with Acute Myocardial Infarction - Subramanian, Usha (Blackwell Science Inc, 2002)
OBJECTIVES: To examine regional variation in health care utilization and outcomes during acute and chronic care of veterans following acute myocardial infarction (AMI), identifying potentially modifiable variables and processes of care that influence patient outcomes. METHODS: Using national VA databases, we identified all veterans hospitalized at any VA Medical Center (VAMC) for AMI between October 1990 and September 1997. Demographic, inpatient, outpatient, mortality, and readmission data were extracted for 4 regions: Northeast, South, Midwest and West. Multivariable Cox proportional hazards regression models, controlled for comorbidity, were used to assess predictors of time to death and readmission. RESULTS: We identified 67,889 patients with AMI. Patient demographic characteristics by region were similar. Patients in the Northeast had more comorbid conditions and longer lengths of stay during the index AMI hospitalization. Region of the country independently predicted time to death, with lower risk of death in the Northeast (hazard ratio [HR] = 0.875; 95% confidence interval [95% CI], 0.834 to 0.918; P < .0001) and West (HR = 0.856; 95%CI, 0.818 to 0.895; P = .0001) than in the South. Patients in the Northeast and West also had more cardiology or primary care follow-up within 60 days and at 1 year post-discharge than patients in the South and Midwest. Outpatient follow-up accounted for a significant portion of the variation in all-cause mortality. CONCLUSION: Substantial geographic variation exists in subsequent clinical care and outcomes among veterans hospitalized in VAMCs for AMIs. Outpatient follow-up was highly variable and associated with decreased mortality. Further studies are needed to explore the causes of regional variation in processes of care and to determine the most effective strategies for improving outcomes after AMI.